The playing-based learning model to improve basic volleyball skills of junior high school students - Samsudin Samsudin; Iwan Setiawan; Dicky Reva Apriana Sanga Dwi (LPMPP Universitas Negeri Yogyakarta, 2023)
This study aims to develop a play-based learning model for basic volleyball techniques and to assess the effectiveness of the volleyball basic technique learning through the approach in improving the learning outcomes on volleyball subject in the juniour high school. The research type was research and development which adopted the 10-step theory of Borg and Gall.. This study used both qualitative and quantitative data analysis. The study designed employed a pretest-posttest control group design to determine the initial abilities of the experimental group and the control group. The significant test of the effectiveness of the basic technique according to play-based volleyball learning model waas rigidly determined by using the t-test. Prior to data analysis, the results of the increase in the experimental group and the control group (n = 40) in the volleyball basics technique were tested for normality using the real level = 0.05.. The results of this study indicate a significant value for the experimental group data of 0.13 and the control group data of 0.09. Because the significant value of the two groups is greater than 0.05, the overall data for the study group is normally distributed. The effectiveness test of the basic techniques of volleyball used the t-test with t count 10.524 and t table 2.024. Accordingly, the basic volleyball techniques of the experimental group was more effective than that of the control group. Junior high school students are thus given an effective and efficient play-based model for learning fundamental volleyball skills.